2019
DOI: 10.1002/masy.201800160
|View full text |Cite
|
Sign up to set email alerts
|

Quenched Polyampholyte Hydrogels Based on (3‐Acrylamidopropyl)trimethyl Ammonium Chloride and Sodium Salt of 2‐Acrylamido‐2‐methyl‐1‐Propanesulfonic Acid

Abstract: A series of polyampholyte hydrogels (PAHs) based on fully charged cationic monomer (3‐acrylamidopropyl) trimethylammonium chloride (APTAC) and anionic monomer sodium salt of 2‐acrylamido‐2‐methyl‐1‐propanesulfonic acid (AMPSNa) were synthesized by free radical copolymerization in the presence of N,N‐methylenebisacrylamide (MBAA) as a crosslinking agent. The functional groups and composition of copolymers were identified by FTIR and 1H NMR spectra. The dynamic swelling properties of PAHs were studied in aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…[7] The displayed band of NHÀ CO (amide group) at 1630 cm À 1 was also observed in the spectrum of HL-MAPTAC polymer. [42] Therefore, the appearance of new peaks for CHL polymers illustrated that the polymerization of lignin with METAC or MAPTAC was successfully achieved.…”
Section: Ftir Spectroscopymentioning
confidence: 95%
“…[7] The displayed band of NHÀ CO (amide group) at 1630 cm À 1 was also observed in the spectrum of HL-MAPTAC polymer. [42] Therefore, the appearance of new peaks for CHL polymers illustrated that the polymerization of lignin with METAC or MAPTAC was successfully achieved.…”
Section: Ftir Spectroscopymentioning
confidence: 95%
“…It was shown that the equimolar PAMPS 82 ‐PAPTAC 83 precipitates in pure water due to the formation of intra‐polyelectrolyte complexes (intra‐PEC) between anionic and cationic blocks while PAMPS 82 ‐PAPTAC 37 and PAMPS 82 ‐PAPTAC 181 containing an excess of anionic and cationic blocks, respectively, are fully water‐soluble. It is supposed that the equal numbers of oppositely charged PAMPS and PAPTAC blocks are involved into formation of a “core,” while the excess of PAMPS and PAPTAC blocks are replaced in a “shell.” It is interesting to compare the behaviors of diblock PAMPS 82 ‐PAPTAC n copolymers with random QPA based on of AMPS m ‐ co ‐APTAC n in aqueous‐salt solutions, where m = 25, 50, and 75 mol%, n = 75, 50, and 25 mol% 46,47 . Equimolar or balanced QPA prepared by RAFT and FRP are insoluble in pure water but dissolved in saline water.…”
Section: Properties Of Quenched Polyampholytes In Water and Aqueous‐salt Solutionsmentioning
confidence: 99%
“…The complexation of charge unbalanced linear and cross‐linked AMPS 25 ‐ co ‐APTAC 75 and AMPS 75 ‐ co ‐APTAC 25 copolymers was studied in aqueous solutions of surfactants and ionic dyes 46 . Complexations of AMPS 25 ‐ co ‐APTAC 75 with the anionic surfactant sodium dodecylbenzenesulfonate (SDBS), and AMPS 75 ‐ co ‐APTAC 25 with the cationic surfactant cetyltrimethyl ammonium chloride (CTMAC) are accompanied by changes in turbidity, zeta‐potential and average hydrodynamic diameter of colloid particles.…”
Section: Complexes Of Quenched Polyampholytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Last year, the present research group focused on quenched, or strongly charged, polyampholytes, based on anionic, AMPS, and cationic, APTAC, monomers, which retain their respective charges independent of pH 15 . The behavior of such polyampholytes in solution 16 and gel state was studied, 17,18 inclusive of their complexation ability with respect to surfactants, dyes and proteins 18,19 . Moreover, they were tested as viscosifying 20 and tracer 21 agents in oil recovery and monitoring well‐to‐well connections.…”
Section: Introductionmentioning
confidence: 99%